Diversity of Hybrid- and Hetero-Pathogenic Escherichia coli and Their Potential Implication in More Severe Diseases - Santos, Ana Carolina de Mello; Santos, Fernanda Fernandes; Silva, Rosa Maria; Gomes, Tânia Aparecida Tardelli (Frontiers in Cellular and Infection Microbiology, 2020)
Although, extraintestinal pathogenic Escherichia coli (ExPEC) are designated by their isolation site, and grouped based on the type of host and the disease they cause, most diarrheagenic E. coli (DEC) are subdivided into several pathotypes, based on the presence of specific virulence traits directly related to disease development. This scenario of a well-categorized E. coli collapsed after the German outbreak of 2011, caused by one strain, bearing virulence factors of two different DEC pathotypes (enteroaggregative E. coli and Shiga toxin-producing E. coli). Since the outbreak, many studies have shown that this phenomenon is more frequent than previously realized. Therefore, the terms hybrid- and hetero-pathogenic E. coli have been coined to describe new combinations of virulence factors among the classic E. coli pathotypes. In this review, we provide an overview of these classifications and highlight the E. coli genomic plasticity that results in some mixed E. coli pathotypes displaying novel pathogenic strategies, which lead to new symptomatology related to E. coli diseases. In addition, as the capacity for genome interrogation has grown in the last few years, it is clear that genes encoding some virulence factors, such as Shiga toxin, are found among different E. coli pathotypes to which they have not traditionally been associated, perhaps, foreshowing their emergence in new and severe outbreaks caused by such hybrid strains. Therefore, further studies regarding hetero-pathogenic and hybrid-pathogenic E. coli isolates are necessary to better understand and control the spread of these pathogens.